MSME MANAGEMENT STRATEGIES IN MUNA REGENCY IN FACING ECONOMIC CHALLENGES - Dano, Muhammad Guntur; Mokodompit, Eliyanti Agus (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The MSME sector in Indonesia plays a significant role in the economy; however, many MSME entrepreneurs still face substantial challenges, particularly in accessing capital, marketing, and business management. In Muna Regency, despite the government's various policies and programs to support MSME management, these challenges remain major obstacles to the development of this sector. Although several studies on MSME management in Indonesia have been conducted, there has been no in-depth study on the effectiveness of MSME management policies, especially in Muna Regency, which has unique economic and social characteristics. This study employs a descriptive qualitative research design with interviews of five key informants involved in MSME management in Muna Regency to analyze the challenges faced and the strategies implemented. The findings of this study provide important insights into the need for more targeted policies and collaboration between the government, financial institutions, and MSME entrepreneurs to address existing constraints, particularly in improving access to financing and expanding markets. The results of this research are expected to contribute to the theoretical development of MSME management literature and offer practical recommendations for government policies and MSME entrepreneurs to enhance competitiveness in the digital era.